2014
DOI: 10.4103/2141-9248.138027
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nutritional status and intensity of common intestinal helminths among children in Enugu, south-east Nigeria

Abstract: Background:Intestinal helminthiasis is associated with malnutrition in children.Aim:The objective of this study was to determine the intensity and effect of the common intestinal helminths on the nutritional status of children in Enugu, Nigeria.Subjects and Methods:A cross-sectional study of 460 children conducted in Enugu metropolis, south-east Nigeria between August and September 2003. Their stools were analyzed at the research laboratory of the Federal Ministry of Health, National Arbovirus and Vector Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
1
1
1
Order By: Relevance
“…Interestingly, we found results contrary to this hypothesis in the study by Ubesie et al 20 in Africa, more specifically in southwestern Nigeria. Sixty-five percent of the children and adolescents were eutrophic, and 2% were underweight.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, we found results contrary to this hypothesis in the study by Ubesie et al 20 in Africa, more specifically in southwestern Nigeria. Sixty-five percent of the children and adolescents were eutrophic, and 2% were underweight.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are similar to previous studies from Nigeria and the Philippines that have documented no significant differences in prevalence of STH infections between malnourished and well-nourished children [18, 31, 32]. By contrast, two other Nigerian studies reported malnourished children to have higher STH prevalence when compared to healthy children [26, 33], while a study among Zairean children reported a lower prevalence in children with SAM [34].…”
Section: Discussionsupporting
confidence: 89%
“…Children in low-income countries are prone to helminth infections (see as an example [ 28 , 39 41 ], a phenomenon suspected to be potentially associated with chronic undernutrition [ 11 , 42 ]. It is surprising that no helminths were found in the stool specimens given the high burden of chronic malnutrition, the still wide-spread use of non-improved well water by 239 of the 414 families (58%) and the socio-economic challenges facing the people of the CAR,.…”
Section: Discussionmentioning
confidence: 99%